Him or her? Choosing competition on behalf of someone else - Helena Fornwagner; Monika Pompeo; Nina Serdarevic (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
We extend the literature on competitive behaviour by investigating environments in which the choice to compete is not made by an individual themselves, but by someone else. Choosing on behalf of others is an integral part of life and gender may be an important factor in shaping the perceived suitability of individuals for career promotions in competitive environments. We assign subjects either the role of an agent or a principal in an experiment. Agents perform a real effort task and a randomly assigned principal chooses whether the agent performs under a piece rate or tournament incentive scheme. Before making a decision for the agent, we vary whether the principal is informed about the agent's gender or not. Regardless of whether gender is revealed, we find no gender gap in competitiveness when principals are choosing for agents. In terms of determinants of the principals' choices, we observe that expectations about their agent's performance, as well as the principal's own preferences for risk and competitiveness matter for the decision to make others compete. In addition, we replicate existing results reporting that women are less willing to enter the tournament than men when choosing themselves. We compare both decision environments and show that efficiency (defined as average performance and earnings) does not suffer, whereas the winners' performance is lower when principals decide for agents. Taken together, our results suggest that allowing others to decide has the potential to increase the representation of women in competitive situations, many of which resemble the labour market.
Keywords: J16; C91; D01; 330; competitiveness; gender differences; decision-making for others; laboratory experiment